QSAR STUDY OF XANTHONE DERIVATIVES AS ANTI PLASMODIAL AGENTS - Amanatie Amanatie; Jumina Jumina; Mustofa Mustofa; M. Hanafi; Ria Armunanto (Indonesian Journal of Chemistry, 2010)
Xanthones and their derivatives have been reported to exhibit inhibitory activities towards Plasmodium falciparum. To provide deep insight into the correlation between inhibitory activities and structures of xanthones, linear regression method was employed to establish QSAR models for 16 xanthone derivatives that have diverse structures. The accuracy and predictive power of the proposed QSAR model were verified by semi empirical PM3 method, optimation, and validation. The result showed that the best model is model 3 i.e. Log 1/IC50 = Σ (-1.446)qO(7)+ (-8.775)q.C(12) + (-10.592)qC(13) + 1,979; Y = PRESS = 1.124192.